Toxic heavy metals removal using a hydroxyapatite and hydroxyethyl cellulose modified with a new Gum Arabic - A Errich; K Azzaoui; E Mejdoubi; B Hammouti; N Abidi; N Akartasse; L Benidire; S EL Hajjaji; R Sabbahi; A Lamhamdi (Indonesian Journal of Science and Technology, 2021)
The objective of this work was to develop a process that allows the synthesis of an apatitic material of controlled composition and morphology, which could be used for medical and environmental applications. The adsorbent was synthesized, and characterized using scanning electron microscopy, nuclear magnetic resonance, Thermal analysis and other techniques, Atomic Force Microscopy, X-ray photoelectron spectroscopy and Total organic carbon. Different experimental parameters such as the effect of the amount of adsorbent, solution pH and temperatures and contact times were studied. Pseudo-order kinetics models were studied, and our data followed a pseudo second order. Experimental data were analyzed for both Langmuir and Freundlich models and the data fitted well with the Langmuir isotherm model. To understand the mechanism of adsorption, thermodynamic parameters like standard enthalpy, standard Gibbs free energy, and standard entropy were studied. The study indicated that the process is spontaneous, exothermic in nature and follow physisorption mechanisms. The novelty of this study showed surface of composite based of hydroxyapatite has the ability to highlight the surface designed for efficient removal of Cu2+ and Zn2+ ions, from aqueous solutions more than other studies.